2005
DOI: 10.1501/tarimbil_0000000571
|View full text |Cite
|
Sign up to set email alerts
|

The Late Spring Frost Hardiness of Some Apple Varieties at Various Stages of Flower Buds

Abstract: Abstract:In this study, survival rates of pistils of seven apple (Malus x domestica Borkh.) varieties at various stages from tight cluster to full bloom on trees were determined after frost that occurred on the morning at 3:00-8:00 of April 17, 2004 when the temperature dropped to -4 to -6 o C in the orchard. The survival rates of pistils of varieties ranged between 36.7 and 96.5% at tight cluster, 6.2 and 86.0 % at first pink and, 0.2 and 52.0 % at full pink stages after frost injury. 'Starkspur Golden Delici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This study demonstrated branches at stage III early bloom, were the most severely damaged by all low temperatures compared to stage II and stage I samples. Freeze/frost injury is highly dependent on the phenological growth stage of the bud/flower ( Aygun and San, 2005 ; Hosseinpour et al., 2018 ). In pecans, freeze induced minimal harm to dormant or enlarged buds, but caused significant damage to buds during the leaf expansion ( Grauke and Pratt, 1992 ; Sparks, 1992 ; Farokhzad et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated branches at stage III early bloom, were the most severely damaged by all low temperatures compared to stage II and stage I samples. Freeze/frost injury is highly dependent on the phenological growth stage of the bud/flower ( Aygun and San, 2005 ; Hosseinpour et al., 2018 ). In pecans, freeze induced minimal harm to dormant or enlarged buds, but caused significant damage to buds during the leaf expansion ( Grauke and Pratt, 1992 ; Sparks, 1992 ; Farokhzad et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low temperature tolerance varies among buds/flowers of different cultivars and species ( Hosseinpour et al., 2018 ). For example, the severity of springtime low temperature damage varies among genotypes/cultivars in almonds, apples, and sour cherry ( Aygun and San, 2005 ; Szpadzik et al., 2009 ; Imani et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%